2016
DOI: 10.1016/j.meteno.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The expression of glycerol facilitators from various yeast species improves growth on glycerol of Saccharomyces cerevisiae

Abstract: Glycerol is an abundant by-product during biodiesel production and additionally has several assets compared to sugars when used as a carbon source for growing microorganisms in the context of biotechnological applications. However, most strains of the platform production organism Saccharomyces cerevisiae grow poorly in synthetic glycerol medium. It has been hypothesized that the uptake of glycerol could be a major bottleneck for the utilization of glycerol in S. cerevisiae. This species exclusively relies on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 30 publications
1
45
0
Order By: Relevance
“…In order to directly compare these yeast species to each other and to S. cerevisiae , we recently performed a growth analysis in synthetic medium containing 6% (v/v) glycerol. One representative strain of Y. lipolytica, C. jadinii, P. tannophilus and K. pastoris was tested, and the values for μ max observed under these conditions were 0.50, 0.42, 0.27 and 0.20 h −1 respectively (Klein et al ., ). Under the same conditions, the best performing wild‐type isolates of the species S. cerevisiae showed growth rates on glycerol of up to 0.15 h −1 (Swinnen et al ., ).…”
Section: Glycerol Utilization By Yeasts: High Inter‐ and Intra‐speciementioning
confidence: 97%
“…In order to directly compare these yeast species to each other and to S. cerevisiae , we recently performed a growth analysis in synthetic medium containing 6% (v/v) glycerol. One representative strain of Y. lipolytica, C. jadinii, P. tannophilus and K. pastoris was tested, and the values for μ max observed under these conditions were 0.50, 0.42, 0.27 and 0.20 h −1 respectively (Klein et al ., ). Under the same conditions, the best performing wild‐type isolates of the species S. cerevisiae showed growth rates on glycerol of up to 0.15 h −1 (Swinnen et al ., ).…”
Section: Glycerol Utilization By Yeasts: High Inter‐ and Intra‐speciementioning
confidence: 97%
“…As was already mentioned in Section , there is limited information on glycerol uptake in O. polymorpha . However, it was shown that introduction of heterologous transporter Fps1 from the yeast K. phaffii in S. cerevisiae improves glycerol utilization in this yeast (Klein et al, ). We attempted to find out glycerol transporters homologs in O. polymorpha .…”
Section: Resultsmentioning
confidence: 99%
“…However, no homologs of Fps1 protein were found in the O. polymorpha database . Nevertheless, we decided to use heterologous gene encoding Fps1 protein, because glycerol transporting capacity of Stl1 in S. cerevisiae is quite low (Klein et al, ). Gene FPS1 of K. phaffii encoding glycerol facilitator was expressed in our best ethanol producing strains.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations